The biomechanical behavior of single crown implant-supported prosthesis with different types of connections and occlusal loads: Photoelastic and strain gauge analysis (Research, Society and Development, 2021)
The aim of the study was to evaluate the biomechanical behavior, through photoelastic (PA) and strain gauge analysis (SA), of single crown implant-supported prosthesis with different implant connections (external hexagon (EH), Morse taper (MT), internal Morse hexagon (IMH), Morse taper hexagon (MTH), and frictional Morse taper (FMT)) and different occlusal loads (axial and oblique (45°)). The data were submitted to ANOVA and Tukey's test (α = 0,05). By photoelasticity, regarding axial load, EH produced more high-intensity fringes (2.784 kPa) than the other connections. For the oblique load, all connections generated the same high-intensity fringes (3.480 kPa), except by MT group, that produced the same amount as axial load (2.088 kPa). For the strain gauge analysis, for the axial load, EH showed the highest microstrains value (158,76) and lowets for MT (59,88). For all other groups, oblique load produced higher microstrains values than axial load. For the oblique load, MT showed the lowest microstrains value (88.79), followed by FMT (391,43), EH (468,47) and IMH (507,65). MTH presented the highest value (621,25) compared to all groups (P